Recombination-mediated escape from primary CD8+T cells in acute HIV-1 infection - Ritchie, A; Cai, F; Smith, N; Chen, S; Song, H; Brackenridge, S; Karim, S; Korber, B; Mcmichael, A; Gao, F; Goonetilleke, N (BioMed Central, 2014)
Background: A major immune evasion mechanism of HIV-1 is the accumulation of non-synonymous mutations in and around T cell epitopes, resulting in loss of T cell recognition and virus escape.Results: Here we analyze primary CD8+ T cell responses and virus escape in a HLA B*81 expressing subject who was infected with two T/F viruses from a single donor. In addition to classic escape through non-synonymous mutation/s, we also observed rapid selection of multiple recombinant viruses that conferred escape from T cells specific for two epitopes in Nef.Conclusions: Our study shows that recombination between multiple T/F viruses provide greater options for acute escape from CD8+ T cell responses than seen in cases of single T/F virus infection. This process may contribute to the rapid disease progression in patients infected by multiple T/F viruses.